ENT and airways in the emergency department: national survey of junior doctors' knowledge and skills. Issue 2 (February 2016) - Whitcroft, K L; Moss, B; Mcrae, A
Abstract: Background: Given the urgent nature of ENT emergencies, appropriate knowledge is required amongst front-line staff. Junior doctors account for almost one quarter of emergency department doctors. It has been shown that undergraduate coverage of ENT is variable. This study therefore aimed to determine whether emergency department junior doctors were confident in dealing with ENT emergencies, with special focus on the airway. Method: An online survey was circulated to junior doctors working in emergency medicine, at the discretion of their training co-ordinators. Results: A total of 104 responses were received. Junior doctors were not confident in managing patients who have undergone tracheostomy or laryngectomy. Management of stridor varied, with 51 per cent giving oxygen and only 77 per cent referring such patients as an emergency to ENT. Most training on the management of airway emergencies was not provided through hospital induction. Conclusion: Training should be provided to junior doctors starting work in the emergency department. We suggest mandatory multidisciplinary induction training for such staff.